2014
DOI: 10.1103/physrevb.90.205404
|View full text |Cite
|
Sign up to set email alerts
|

Density of states at disorder-induced phase transitions in a multichannel Majorana wire

Abstract: An N-channel spinless p-wave superconducting wire is known to go through a series of N topological phase transitions upon increasing the disorder strength. Here, we show that at each of those transitions the density of states shows a Dyson singularity ν(ε) ∝ ε −1 | ln ε| −3 , whereas ν(ε) ∝ ε |α|−1 has a power-law singularity for small energies ε away from the critical points. Using the concept of "superuniversality" [Gruzberg, Read, and Vishveshwara, Phys. Rev. B 71, 245124 (2005)], we are able to relate the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…Energy spectrum and Majorana energy splitting Disordered Kitaev chains have formed the topic of active research for over a decade for several reasons [36][37][38][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] . Belonging to the symmetry classes D and BDI (depending on whether they respect time reversal symmetry breaking or not), these systems exhibit behavior that starkly deviates from that of their normal counterparts.…”
Section: Fermion Parity Switches and Low-energy States In Finite-smentioning
confidence: 99%
See 2 more Smart Citations
“…Energy spectrum and Majorana energy splitting Disordered Kitaev chains have formed the topic of active research for over a decade for several reasons [36][37][38][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] . Belonging to the symmetry classes D and BDI (depending on whether they respect time reversal symmetry breaking or not), these systems exhibit behavior that starkly deviates from that of their normal counterparts.…”
Section: Fermion Parity Switches and Low-energy States In Finite-smentioning
confidence: 99%
“…Several investigations on the distribution of these mid-gap states have explored scaling of density-of-states in Griffiths phases, transport properties and topological phase transitions in the context of disordered Majorana wires. [36][37][38][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] . Here, as a simple illustration, in Fig.…”
Section: Fermion Parity Switches and Low-energy States In Finite-smentioning
confidence: 99%
See 1 more Smart Citation
“…One theoretically explored an interferometry of a chiral Majorana edge channel formed at the interface between a superconductor and a topological insulator under an external magnetic field, quantum-transport properties can manifest the obvious signatures of Majorana modes [29]. Since quantum dots(QDs) as the artificial granules can provide an excellent model system to study quantum transport behaviors, very recently, the searches for Majorana quasi-particles have become a focus of intense attention based on the granular QD devices [20,[31][32][33][34]. A scheme for manipulating the MBS has been addressed based on Coulomb blockaded quantum dots(QDs), it is found that the QDs may be utilized for readout of the state of the Majorana system [35].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most promising candidate proposals for the full demonstration of MFs is to use semiconducting nanowires(InAS or InSb wires) with a strong spin-orbit interaction, where a nanowire is placed in proximity to a superconductor and biased with a magnetic field. For a one-dimensional topological superconductor(TS) quantum wire, Majorana modes are localized at the edge of the nanowire, some experimental realizations have been recently reported that the search for MFs has been successful in semiconductor wires on superconducting surfaces [18][19][20][21][22]. Certainly, other alternative routes to detect the properties of MFs and manipulate them also are provided including noise measurements [23], resonant Andreev tunneling [24], the 4π-periodic MajoranaJosephson effect [25], the phase-related electric conductance [26], and so forth.…”
Section: Introductionmentioning
confidence: 99%